Gross anatomical study of the subcutaneous structures that create the three‐dimensional shape of the buttocks. Issue 2 (28th December 2022) - Han, Aya; Inoue, Eiko; Kikuchi, Keishiiro; Haikata, Yuto; Tabira, Yoko; Iwanaga, Joe; Saga, Tsuyoshi; Kiyokawa, Kensuke; Watanabe, Koichi
Abstract: The purpose of this study was to clarify the subcutaneous structures involved in the morphology of the gluteal region for clinical application. Thirty‐seven formalin‐fixed cadavers and one soft‐fixed cadaver were used in this study. Gluteal tissue was removed from five formalin‐fixed cadavers. A horizontal section and sections parallel to the long axis of the body were made from the excised tissue, and the subcutaneous fat was removed to observe the fibrous structure within the subcutaneous fat. Two formalin‐fixed cadavers and one soft‐fixed cadaver were used to perform conventional gross anatomical dissection and histological examination. On 30 formalin‐fixed cadavers, the thickness of the subcutaneous fat was measured in various areas of the buttocks. The thickness of subcutaneous fat was thicker in the center of the buttocks and thinner on the lateral buttocks. Superficial fascia (SF) was found only in the upper buttock, being indistinct in the lower buttock. In the sacral and coccygeal areas, the dermis was tightly adhered to the bone as a single mass. Fibers arose from around the iliac crest to the SF. On the medial side of the gluteal fold, a strong fiber arose from the sciatic tubercle and inserted into the gluteus maximus and dermis. By identifying the characteristic subcutaneous structures of the gluteal region, we were able to identify the anatomical structures that shape the three‐dimensional morphology of the buttocks. These findings may be useful in surgical treatments such as improving the buttock shape.